Synthesis of Co-doped ZnO/Ag Heterostructure for Photocatalysis Application - Ahmed Mohammed (ASTU, 2025)
The inclusion of cobalt ions into the ZnO lattice and the formation of a ZnO/Ag Schottky barrier at the heterojunction can considerably improve photocatalytic potential. Here in this study, Co-doped ZnO/Ag heterostructure was synthesized using a simple sol-gel combustion approach. The PVA-CZS complex TGA-DTA thermal stability analysis result confirmed that 400°C was found to be the temperature at which stable Co-doped ZnO/Ag heterostructure material was obtained. The appearance of independent silver peaks on the X-ray diffraction pattern confirms the formation of a ZnO/Ag Schottky barrier. The nonexistence of a cobalt (II, III) oxide independent peak and the presence of a high-angle peak shift confirms greater solubility of cobalt ions in the ZnO lattice. Besides, the formation of the ZnO/Ag Schottky barrier was affirmed by the HRTEM image d-spacing analysis for ZnO (0.262 nm) and Ag (0.233 nm) crystals. The reduction of indirect DRS-UV-vis bandgap energy for CSZ (2.63 eV), compared to ZnO (3.15 eV), also supports the cobalt ion inclusion in ZnO lattice. Besides, the CZS PL spectra intensity reduction compared to ZnO confirms the presence of charge transfer through the ZnO/Ag Schottky barrier. Thus, it’s possible to conclude that, the CZS has better visible light absorption and charge transfer properties than ZnO nanoparticles (NPs). The FESEM morphological analysis shows the formation of a cotton type porous CZS heterostructure. EDS-elemental compositional and elemental mapping analysis images confirmed the presence of only expected elements with good dopant distribution on the ZnO host surface. The CZS HSs exhibited improved photocatalytic degradation of methylene blue dye (k=0.0786 min-1) compared to ZnO (k=0.02 min-1). The improvement of photocatalytic potential is associated with the improved light absorption and charge transfer ability of CZS HSs materials.
Keywords: Co-doped ZnO/Ag heterostructure, methylene blue degradation, photocatalysis, Charge transfer